War and Remembering Among Italian-Canadian Writers - Pivato, Joseph (Italian Canadiana, 2023)
In this paper, we will examine the connection between the Second World War and Italian-Canadian literature. Many early works from this literature had their roots in the devastation of war in Italy and the resulting mass migration of thousands of Italians to Canada in the 1950s and 1960s. After writing about the initial immigrant experience, most Italian-Canadian authors moved on to other topics and themes. Some wanted to become more Canadian and less Italian in orientation. In later years, some of these authors returned to the topic of the war and its long-term effects on their lives. We will begin our examination by looking at some examples of how war is treated in early works and then we will consider the phenomenon of how the war is revisited in later works.